Correlation of muscular strength and balance in relation to single leg squat analysis in male football players – an observational study - Mrugnayani Chandrashekhar Patil; Sarath Babu (Physiotherapy Quarterly, 2024)
Introduction Individual participation in sports with inadequate preparation, especially during competition, results in an increased incidence of injury. Athletes commonly suffer from lower extremity musculoskeletal pain. During growth, several biomechanical factors contribute to muscular imbalance, which results in injury. The aim of the current study was to determine the correlation between lower extremity strength and balance in relation to single leg squat depth.